2011
DOI: 10.1029/2011jb008651
|View full text |Cite
|
Sign up to set email alerts
|

Charge mechanism of volcanic lightning revealed during the 2010 eruption of Eyjafjallajökull

Abstract: Volcanic lightning has intrigued observers through the centuries. Several likely processes have been proposed to explain the electrification of volcanic plumes, including quenching magma‐water interactions, the fracturing or internal friction of fine grained ash, and the freezing of plume water at height. Scarce measurements of volcanic lightning have not been able to distinguish between proposed ideas. The Eyjafjallajökull volcanic eruption in Iceland in April–May 2010 may have revealed its charge mechanism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 38 publications
(50 reference statements)
5
60
0
1
Order By: Relevance
“…The second interval, when relatively high rates of lightning were observed, occurred between 11 and 21 May. This distinction was also observed by Bennett et al [] and Arason et al [] in the ATDnet data.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The second interval, when relatively high rates of lightning were observed, occurred between 11 and 21 May. This distinction was also observed by Bennett et al [] and Arason et al [] in the ATDnet data.…”
Section: Resultssupporting
confidence: 78%
“…The figure shows that it was significantly warmer during 5–10 May, when very little lightning was observed, than it was from 11 to 21 May, when high rates of lightning were observed (with the exception of a brief increase in temperature on 12 May). This correlation has already been described by Arason et al [], who compared plume top temperatures (derived by comparing the radar data to the atmospheric data from the UM) to the ATDnet‐detected lightning rates and found that higher rates of lightning occurred with decreasing plume top temperatures. This led Arason et al [] to conclude that plume‐based ice‐contact charging was likely responsible for the lightning detected by ATDnet.…”
Section: Resultssupporting
confidence: 76%
“…Lightning was extensively documented during the explosive phase of the Mount Redoubt eruption using the lightningmapping array (Rison et al, 1999;Thomas et al, 2004;Behnke et al, 2013) and throughout the explosive phase of the 2010 Eyjafjallajökull eruption by the UK Met Office (www.metoffice. gov.uk) long-range lightning location network (Bennett et al, 2010;Arason et al, 2011). Two pseudo-ash samples that replicated the chemical, physical, and electrical properties of freshly fallen ash were bulk manufactured using the procedure developed by Wardman et al (2012b) for the flashover experiments (details are pro- vided in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this paper is to present evidence from observations of the impact of the atmosphere on an eruption plume of a medium‐size explosive eruption, from the larger scale features controlling the downstream advection and dispersion of volcanic ash to the small scale features of the convective phase of the plume. Another example of the impact of the ambient atmosphere on the Eyjafjallajökull eruption plume is given by Arason et al [2011b] where it is suggested that the ambient atmospheric temperature had significant impact on lightning activity in the plume. The arrival of the ash from Eyjafjallajökull 2010 over the continental Europe is a subject of numerous papers, based on both observations and model simulations [e.g., Dacre et al , 2011; Devenish et al , 2012; Emeis et al , 2011; Schumann et al , 2011], and is outside the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%